Purchasing food to counteract Mafia in Italy. Issue 2 (15th November 2017) - Rivaroli, Sergio; Ruggeri, Arianna; Novi, Pietro; Spadoni, Roberta
Abstract : Purpose: The paper aims to investigate pro-social behaviour of Italian consumers during the decision-making process of buying food produced in lands confiscated from Mafia-type organisations. This is assumed as a form of buycotting, thus as an ethical purchasing choice to contribute to social change. Design/methodology/approach: Data from 339 interviews were elaborated with a cluster analysis. The difference between groups was confirmed using MANOVA, whereas the multivariate multiple regression analysis was carried out to assess the difference between clusters. Findings: Three types of consumer groups are identified: absolutists, exceptionist s and subjectivists . Coherent with previous studies, findings also highlight the relevance of information acquisition and of the self-effectiveness perception as key factors to stimulate pro-social behaviours. Originality/value: With a social marketing perspective, the paper offers useful suggestions to promote political consumerism as a critical choice to contribute to fight against Mafia-type organisations and to spread a culture of lawfulness.